Peculiarities Of Legal Regulation Of The Application Of Legal Principles In The Processes Of Lawmaking And Law Enforcement: Comparative Analysis - Lezhnieva, Tetiana; Moseiko, Anzela; Samoilenko, Oleksandr; Kuzyk, Viacheslav; Yеrmenchuk, Oleksandr; Yеrmenchuk , Oleksandr (Jurnal Cita Hukum, 2026)
The work is aimed at a comprehensive analysis and justification of the mechanisms for applying the principles of law in the processes of lawmaking and law enforcement. The main attention is paid to the study of how fundamental legal ideas are transformed into effective instruments for regulating social relations, ensuring the integrity and logic of the legal system. During the study, it was established that the principles of law are not purely formal constructs. They should be interpreted as universal, fundamental and basic provisions that reflect the deep foundations of human existence. These ideas are the product of long-term social interaction and reflect the general relations that are formed between the participants in legal relations. Acting as a kind of "genetic code" of law, these principles form the basis for sustainable legal development, determining the boundaries of permissible behavior and the vector of development of legislative initiatives. To achieve the set goal and ensure the objectivity of the results, a systematic approach and a number of scientific methods were used: analysis of biographical and primary sources: to study the evolution of views on legal ideologemes; synthesis and deduction: to form a holistic view of the role of principles on the basis of individual legal phenomena. The results of the study prove that consistent and systematic adherence to legal principles by law-making and law-enforcement bodies is a key condition for creating an atmosphere of predictability and stability in the legislative field. The effectiveness of the legal system directly depends on the recognition of the principles of law as norms of direct action that have the same regulatory force as specific legal regulations that regulate highly specialized relations